2016
DOI: 10.4158/ep15670.cr
|View full text |Cite
|
Sign up to set email alerts
|

Development of Abnormal Pigmentation of the Oral Mucosa Following Adjuvant Radioactive Iodine Treatment

Abstract: Objective:We report the case of a 52-year-old black woman who developed discoloration of her tongue following radioactive iodine (RAI) ablation. RAI is a common method of treatment for a number of thyroid disorders, including thyroid malignancies and hyperthyroidism. Common side effects of this therapy include hypothyroidism, changes in taste, nausea, and sialadenitis.Methods: This is an Institutional Review Boardapproved single-case chart review with a patient consent.Results: The patient presented with no ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Most common early side effects of this therapy are nausea, sialadenitis, dry mouth and changes in the taste sensation, salivary gland pain, salivary gland swelling and vomiting (1)(2)(3)(4). Black pigmentation of tongue following RAI therapy is an extremely rare side effect and there are very few cases documented worldwide till now, we found only two reported cases (5,6). Exact etiology of back pigmentation of tongue following RAI therapy is unknown.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…Most common early side effects of this therapy are nausea, sialadenitis, dry mouth and changes in the taste sensation, salivary gland pain, salivary gland swelling and vomiting (1)(2)(3)(4). Black pigmentation of tongue following RAI therapy is an extremely rare side effect and there are very few cases documented worldwide till now, we found only two reported cases (5,6). Exact etiology of back pigmentation of tongue following RAI therapy is unknown.…”
Section: Introductionmentioning
confidence: 80%
“…This patient presented with black discoloration of the dorsum of the tongue, which is most consistent with post-RAIT. Since the beginning of RAI therapy in 1946, this case indicates one of the rarest side effects following RAI therapy (5). Regarding a mechanism by which RAI could induce pigmentation of the tongue, one study found that the tongue lacks expression of the sodium iodide symporter (6).…”
Section: Discussionmentioning
confidence: 97%